Prevalence and risk factors for superinfection with a difficult-to-treat pathogen in periprosthetic joint infections - Darwich, Ali; Baumgärtner, Tobias; Hetjens, Svetlana; Gravius, Sascha; Bdeir, Mohamad (Antibiotics, 2025)
Background: Periprosthetic joint infections (PJIs) are considered as one of the most serious complications after total joint arthroplasty. Aim of this study was to evaluate the prevalence of PJI caused by difficult-to-treat (DTT) pathogens as well as PJIs with a superinfection with a DTT pathogen in the course of the infection and assess the risk factors leading to this emergence. Methods: Data of 169 consecutive patients with a PJI was analyzed in this retrospective observational single-center study, and cases were categorized into PJIs with initial DTT pathogens, PJIs with DTT pathogen superinfection, non-DTT PJIs, and PJIs with superinfection. Recorded parameters comprised age, gender, side, body mass index (BMI), preoperative anticoagulation, and serum level of C-reactive protein (CRP) at admission, as well as preoperative patient status using the ASA (American Society of Anesthesiologists) score and the age-adjusted form of the Charlson comorbidity index (CCI). Furthermore, the infecting microorganism and the type of infection as well as the chosen operative treatment regime, duration of the antibiotics interval, and the outcome were recorded. Results: In total, 46.2% of cases were DTT PJIs, and 30.8% of them were superinfections. Elevated serum CRP levels at admission (≥92.1 mg/L) were linked to a nearly 7-fold increased likelihood of a DTT PJI (OR 6.981, CI [1.367-35.63], p = 0.001), compared to patients with a non-DTT PJI. Hip joint involvement was also associated with a 3.5-fold higher risk compared to knee joints (OR 3.478, CI [0.361-33.538], p = 0.0225). Furthermore, patients undergoing ≥3 revision surgeries demonstrated a significantly 1.3-fold increased risk of developing a DTT superinfection (OR 1.288, CI [1.100-1.508], p < 0.0001). Chronic PJIs were similarly associated with a markedly 3.5-fold higher likelihood of superinfection by DTT pathogens (OR 3.449, CI [1.159-10.262], p = 0.0387). Remaining parameters did not significantly affect the rate of a DTT PJI or a PJI with DTT superinfection. Conclusions: These findings underscore the importance of early identification of high-risk patients and highlight the need for tailored preventive and therapeutic strategies in managing DTT PJIs.